Poligami dalam Hukum Islam: Kajian Atas Dampak Sosial dan Ekonomi terhadap Keharmonisan Rumah Tangga - Marbujang; Putrado Herliansyah; Suweknyo; Handika Utama Putra; Mita Mauli Nanda (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
Polygamy is an interesting issue to discuss in the study of Islamic Family Law. This is because the discussion of polygamy has its own polemics. From the phenomenon of polygamy practices that are currently occurring, the author wants to explore and explore the Impact of Polygamy on Social and Economics in Household Harmony. Exploring the impact of polygamy does not mean disagreeing with the practice of polygamy. However, to find out the impact of the practice of polygamy itself. As this is the purpose of this study. The importance of studying this is to find out the impact of polygamy practices that occur in society comprehensively, both from social and economic impacts. In this study, the author uses the type of research (library research) Literature or literature review. In this study, the results of the study were found on the Impact of Polygamy Practices on Social and Economics in Household Harmony, including the strained relationship between the father and the first wife and children due to the presence of a new person in the household, which will then affect the stability of the peace of mind of the first wife and children due to disappointment with a father because of polygamy even though they know that polygamy is allowed. And automatically the economic income of a father is also divided, as well as the affection of a father because the income from shopping and affection must be divided among all families.